Persistently High Incidences of Trypanosoma brucei rhodesiense Sleeping Sickness With Contrasting Focus-Dependent Clinical Phenotypes in Malawi - Nambala, Peter; Mulindwa, Julius; Chammudzi, Priscilla; Senga, Edward; Lemelani, Marshal; Zgambo, Drifton; Matovu, Enock; MacLeod, Annette; Musaya, Janelisa (Frontiers in Tropical Diseases, 2022)
Background Human African trypanosomiasis (HAT) has caused social–economic burden in remote rural communities mostly in sub-Saharan Africa for over a century. The World Health Organization had targeted the year 2020 for the elimination of HAT caused by Trypanosoma brucei rhodesiense, which is mainly endemic in Malawi, Uganda, Tanzania, and Zambia. Significant progress has been made in reducing reported HAT cases in some countries. Area-specific updated epidemiological and clinical data may facilitate in understanding the progress of such efforts as well as the development of new intervention strategies. Methods We analyzed HAT prevalence and demographics from epidemiological surveys carried out from 2012 to 2020 obtained from the Ministry of Health, Malawi. In addition, we analyzed blood samples and clinical profiles of HAT patients surveyed between 2016 and 2020 from Rumphi and Nkhotakota districts. From the blood samples, parasite observations and speciation were carried out, whereas disease staging and severity were ascertained from the clinical profiles. Results Malawi reported 315 HAT cases from 2012 to 2020. The majority of HAT cases were men (70.2%), and the mean age was 29.9 ± 15.3 with all HAT fatalities resulting from stage 2 disease. Clinical symptoms were not significantly associated with disease outcome; however, swollen lymph nodes (p = 0.004), weight loss (p = 0.010), headache (p = 0.019), and sleep disturbance (p = 0.032) were significantly associated with the HAT stage of patients. About 50% of all HAT patients were reported within 2 years from 2019 to 2020, suggesting a HAT outbreak in Malawi. Conclusion This study has highlighted the current epidemiological insights of the rHAT trend in Malawi. We have shown that rHAT clinical phenotypes in Malawi are focus-dependent and that there has been a steady increase in rHAT cases compared to all countries with incidences of rHAT. We have also highlighted an outbreak of rHAT that occurred in Malawi from 2019 to 2020 with almost 50% of the total rHAT cases that we have presented in this study reported within 2 years of the outbreak. These should call for a review of Malawi’s rHAT control and elimination strategies. A One-Health approach with the inclusion of key stakeholders such as the department of parks and wildlife may also be considered.